The relationship between cognitive function and functional capacity, and cognitive reserve and reaction time in patients with multiple sclerosis - Busra Candiri; Engin Ramazanoglu; Burcu Talu; Mehmet Tecellioglu (Arquivos de Neuro-Psiquiatria)
Background Cognitive dysfunction is frequently seen in multiple sclerosis (MS). However, there are conflicting findings regarding the factors it is associated with.